MENANAMKAN KEDISIPLINAN MELALUI PENDEKATAN BEHAVIOR OLEH GURU BIMBINGAN DAN KONSELING DI SMK BHAKTI BANGSA BANJARBARU - Julfi, Muhammad; irhamni, irhamni (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2018)
This research is based on phenomena that occur in the Bhakti Bangsa Vocational School which shows that many students commit violations and school rules. The purpose of this research is to overcome school undisciplined behavior through counseling with contractual engineering behavioral approaches.The type of research used is handling cases. Research focus is behavior that often violates discipline. Data collection methods used are observation, interviews and documentation. Data analysis used is data reduction, data review and description. Research subjects are students who have undisciplined behavior problems.The results showed that the fourth counseling before counseling had undisciplined behavior in school. There are students caught storing indecent videos so that they are embarrassed and do not want to go to school for a few days, often do not go to class without explanation, often skip school because they like to play online games at the cafe, often go home sooner before the school bell rings. After being given counseling services with behavioral contractual behavioral approach, counselees begin to understand the importance of school.Overall counseling conclusions on counselees who have undisciplined behavior can be overcome through individual counseling with a contractual behavioral approach. It is proven that there are behavioral changes that are not disciplined to be more disciplined. School counselors are expected to be able to overcome the problem of students through counseling and guidance services, especially counseling with a contractual behavioral approach to address undisciplined behavior, accompanying, motivating and always monitoring the counselee's progress in order to continue to commit to no more school discipline violations. The headmaster is expected to be able to facilitate the counselor in the implementation of guidance and counseling services and supervise the development of problematic students. Keywords: Discipline, Behavior Approach, Guidance and Counseling Teachers